An improved single cell ultrahigh throughput screening method based on in vitro compartmentalization. - Fuqiang Ma; Yuan Xie; Chen Huang; Yan Feng; Guangyu Yang (PLoS ONE)
High-throughput screening is a key technique in discovery and engineering of enzymes. In vitro compartmentalization based fluorescence-activated cell sorting (IVC-FACS) has recently emerged as a powerful tool for ultrahigh-throughput screening of biocatalysts. However, the accuracy of current IVC-FACS assays is severely limited by the wide polydispersity of micro-reactors generated by homogenizing. Here, an improved protocol based on membrane-extrusion technique was reported to generate the micro-reactors in a more uniform manner. This crucial improvement enables ultrahigh-throughput screening of enzymatic activity at a speed of >10⁸ clones/day with an accuracy that could discriminate as low as two-fold differences in enzymatic activity inside the micro-reactors, which is higher than similar IVC-FACS systems ever have reported. The enzymatic reaction in the micro-reactors has very similar kinetic behavior compared to the bulk reaction system and shows wide dynamic range. By using the modified IVC-FACS, E. coli cells with esterase activity could be enriched 330-fold from large excesses of background cells through a single round of sorting. The utility of this new IVC-FACS system was further illustrated by the directed evolution of thermophilic esterase AFEST. The catalytic activity of the very efficient esterase was further improved by ∼2-fold, resulting in several improved mutants with k(cat)/K(M) values approaching the diffusion-limited efficiency of ∼10⁸ M⁻¹s⁻¹.